Revitalizing Indonesia’s agriculture: an examination of the economy-wide effects of policy changes - Firmansyah (Curtin University, 2013)
This thesis aims to examine the economy-wide effects on Indonesia’s macro-economy, industries and households of policy changes embodied in its agricultural revitalization program. The thesis develops a 52-sector, recursive dynamic computable general equilibrium model of the Indonesian economy which decomposes the agricultural sector to 26 industries. Of particular interest to this thesis are the analyses of the potential impacts of various policy scenarios involving tariff and subsidy changes, and an increase in agricultural productivity.